The Effect Of Random Word Game In Improving English Vocabulary - Evi Kartini Putri; Muhammad Hanafi; Sam Hermansyah; Nuraini K (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2021)
The purpose of this study was determined whether the use of random word games could improved the ability of SMP N 2 Pancarijang students in vocabulary and whether students are interested in the method of this game. This study uses a mixed research method that was a quantitative research. The population of this study was seventh grade students of SMP N 2 Pancarijang in the 2018-2019 academic year. The total population was 87 students consisting of 4 classes. Class VII3 was taken as a sample using cluster sampling techniques, the total number of samples was 21. The instruments used in this study were vocabulary tests.The results of this study indicate that the pre-test got an average score (29,28) while the post-test got an average score (52,85). This shows that there was a significant difference between the pre-test and post-test. The p-value (0,00) is lower than the significant level (alpha (Î±) = 0,05). This means H1 was accepted. This study concluded that vocabulary teaching using the random word game improved students' ability to master vocabulary mastery in seventh grade students of SMP N 2 Pancarijang.